The application of genomics and transcriptomics for the characterization of the genetic diversity of tick-resistance in Angus, Brahman, Nguni, and Santa Gertrudis cattle artificially infested with Rhipicephalus microplus and Rhipicephalus decoloratus - Marima, Jacqueline Keena (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.